2007
DOI: 10.1128/jvi.01403-06
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Rapid Spread of Human Immunodeficiency Virus Type 1 BF Recombinants in Argentina

Abstract: The epidemic of human immunodeficiency virus type 1 (HIV-1) in Argentina is distinctive in that many infections are caused by subtype BF recombinant viruses. To determine their demographic history, we estimated the evolutionary rate, mode of population growth, and age of genetic diversity among 40 BF vpu sequences. This revealed one of the highest substitution rates reported for HIV-1, at 10.793 ؋ 10 ؊3 substitutions per site per year, and a very rapid rate of population growth, with an initial mean epidemic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 13 publications
5
16
1
Order By: Relevance
“…Interestingly, several studies [Aulicino et al, 2007;Bello et al, 2010;Dilernia et al, 2011] have reported recently that the origin of the HIV-BF subtype in South America dates from the beginning of the 1970s, overlapping with the HPD 95% found for the HCV-1a Argentinean sequences included into the cluster M. Nevertheless, the 95% HPD intervals found for the tMRCA of the HCV-1a cluster, final conclusions remain elusive. This limitation deserves further investigation with a longer time span of sampling that allows reaching short confidence intervals for dates, and higher precision.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, several studies [Aulicino et al, 2007;Bello et al, 2010;Dilernia et al, 2011] have reported recently that the origin of the HIV-BF subtype in South America dates from the beginning of the 1970s, overlapping with the HPD 95% found for the HCV-1a Argentinean sequences included into the cluster M. Nevertheless, the 95% HPD intervals found for the tMRCA of the HCV-1a cluster, final conclusions remain elusive. This limitation deserves further investigation with a longer time span of sampling that allows reaching short confidence intervals for dates, and higher precision.…”
Section: Discussionmentioning
confidence: 98%
“…Although initially it was thought that the South American subtype C epidemic was founded by viruses from Burundi, a country that does not share social, cultural, or economic relations with any South American country, it was later found to be linked to a small subtype C epidemic in the United Kingdom, a country which shares strong ties with Brazil (de Oliveira et al 2010). Subtype F was thought to be introduced into South America in the late 1970s, and a BF1 recombinant rapidly spread, becoming the dominant virus in Argentina (Aulicino et al 2007). …”
Section: The Spread Of Hiv To South Americamentioning
confidence: 99%
“…Our findings are in line with the fact that subtype B has a lower vitality when exposed to Nelfinavir than AE variants [34]. Moreover, BF CRF forms with F protease show a high rate of growth rate in Argentina [35] and Uruguay [36] which would be explained to some extent by a higher F proteases vitality.…”
Section: Overall Differences Between Subtype B and Subtype F Proteasessupporting
confidence: 87%